Impact of Implant Angulation on Stress Distribution and Survival Rate of Implant-Supported Fixed Dental Prostheses: A Prospective Clinical Study - Ojas Anand Gajbhiye; Vishal B. Parmar; Fouziya Begum; Syed Mehmood Hussaini; Sarath Chandra; Sonikumari (Journal of Pharmacy and Bioallied Sciences)
Background: Dental implantology has witnessed substantial progress, particularly with the widespread use of implant-supported fixed dental prostheses (FDPs) for edentulous patients. Methods: In this prospective clinical study involving 146 adult participants requiring implant-supported FDPs, a randomized allocation placed individuals into either the control group (ideal angulation) or the experimental group (deviated angulation). A comprehensive investigation unfolded through finite element analysis (FEA), examining biomechanical aspects. This was complemented by thorough clinical assessments and the collection of patient-reported outcomes. Results: The application of FEA unveiled a statistically significant increase in the maximum von Mises stress within the experimental group (P = 0.032), suggesting a tangible impact of deviated angulation on stress distribution. However, when transitioning to the clinical realm, the evaluation of implant stability, osseointegration, and prosthetic fit demonstrated no significant differences between the control and experimental groups. Patient-reported outcomes demonstrated no statistically significant differences in comfort, aesthetic satisfaction, or overall satisfaction between the control and experimental groups (all P > 0.05). Conclusion: While finite element analysis identified biomechanical differences associated with deviated implant angulation, these distinctions did not consistently translate into clinically significant variations.